Hydrophilic group-containing high-biodegradability polyester and preparation method thereof

By introducing highly hydrophilic groups into aromatic polyester to enhance its hydrophilicity, the problem of poor biodegradability of aromatic polyester is solved, achieving high biodegradability and excellent thermal properties, mechanical properties and processing Performance balance.

CN119350602APending Publication Date: 2025-01-24ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411429411.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing aromatic polyester materials have poor biodegradability, which makes them difficult to degrade after their service life, causing environmental pollution.

Method used

By introducing high-ended water-based groups in the low-fat content fat-aromatherapy cluster, enhance the hydrophilicity of the polymer, thereby achieving high biodegradability under the content of the low-fat chain segment.

Benefits of technology

It achieves a high biodegradation rate (more than 98%) of copolyester in an industrial composting environment, while retaining the excellent thermal, mechanical and processing properties of aromatic polyester.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083187290000091
    Figure BDA0005083187290000091
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and provides high-biodegradability polyester containing hydrophilic groups and a preparation method of the high-biodegradability polyester aiming at the problem that aromatic polyester polymers are poor in biodegradability, and the preparation method comprises the following steps: (1) taking a first reactant, a second component, terephthalic acid and ethylene glycol as raw materials, carrying out esterification or ester exchange reaction to obtain ester; the first reactant is a polyfunctional group small molecule with a hydrophilic group and two additional linking sites; the second component is aliphatic polyhydric alcohol, polybasic acid, polyhydric alcohol acid or ester; and (2) carrying out condensation polymerization on the esterified product to obtain the high-biodegradability polyester. The crystallinity of the polyethylene terephthalate is 50% or above of that of polyethylene terephthalate, the glass transition temperature is higher than 65 DEG C, the 5% thermal weight loss temperature is 380 DEG C or above, and the 180-day biodegradation rate is 98% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to a highly biodegradable polyester containing a hydrophilic group and a preparation method thereof. Background Art

[0002] Aromatic polyester polymers are obtained by the polymerization of aromatic polyacids and polyols. The high stability brought by the ester bonds composed of benzene rings and benzoyl groups and the easy design of high crystallinity structures make it a type of engineering plastics with excellent performance and wide applications. For example, polyethylene terephthalate (PET), as one of the most produced and used synthetic polymers in the world, is widely used in textiles, packaging, electronic information and other fields due to its good mechanical properties and processability and stable product performance. However, the stable structure also makes the product difficult to degrade. At the end of its service life, it can only be disposed of by landfill or incineration in landfills, affecting terrestrial and aquatic ecosystems and posing environmental challenges. In addition, non-degradable plastic products have become an important source of microplastics, and the negative impact on the environment and human health is constantly being revealed as research deepens.

[0003] Therefore, in recent years, many works have focused on the development of biodegradable aliphatic (co) polyester products. The design paths of these polyesters are very similar, that is, by using short aliphatic ester chains that are more easily hydrolyzed, polyesters or copolyesters are formed to obtain biodegradable polyester products. Single aliphatic polyesters, such as polybutylene succinate (PBS), polybutylene adipate-succinate (PBSA), polypropylene carbonate (PPC), polycaprolactone (PCL), polylactide (PLA), polyglycolide (PGA), polyhydroxyalkanoate (PHA), etc., have excellent biodegradability. However, there are inherent defects such as poor mechanical properties, too low glass transition temperature, and difficult molding and processing. It is difficult to compare with traditional polymers in terms of comprehensive performance, so its application is limited. Copolymerizing these aliphatic chains with aromatic polyacids through copolymerization methods is an effective way to construct biodegradable polyesters. The successfully developed polybutylene adipate-terephthalate (PBAT) and polybutylene succinate-co-terephthalate (PBST) show good biodegradability. However, this method has high requirements for the content of aliphatic chains. The desired biodegradation rate can only be achieved when the molar content of aliphatic chains is more than half or close to half of the whole chain. These aliphatic flexible chains seriously damage the regularity and structural stability of the chain, resulting in a significant decrease in mechanical properties. How to achieve high biodegradability while retaining the various good performance advantages of aromatic polyesters while adding as few flexible chains as possible is an unresolved problem.

[0004] Structural factors that affect biodegradability include molecular chain structure and composition. In addition, its molecular weight, crystallinity, and material form will also affect the speed of its biodegradation. The changes in chemical structure have a greater impact on its biodegradability. In addition to inserting more easily hydrolyzed segments, the design of improving the biodegradability of aromatic polyester materials from the perspective of improving hydrophilicity has not yet been taken seriously. Hydrophilicity and hydrophobicity are important for material biodegradability because during the degradation of materials, microorganisms first need to attach to the surface, and then release a variety of enzymes to further erode the material. After the molecular weight is degraded to below 500D, it can be used by microorganisms. Most microorganisms survive in an aquatic environment. The hydrophobic surface makes it difficult for microorganisms to attach to form a biofilm, which hinders further erosion and decomposition by microorganisms. Modifying the molecular chain to hydrophilicity is expected to improve biodegradability. CN1980976A, CN1980977A, CN1829759A, CN101735438A, and CN111848937A disclose sulfonated copolyether ester compositions containing hydroxyalkanoic acid and methods for preparing the sulfonated aromatic copolyether esters, which contain benzenesulfonate, and the polymers exhibit biodegradable properties, but do not involve other hydrophilic groups. Summary of the invention

[0005] In order to overcome the problem of poor biodegradability of aromatic polyester polymers, the present invention provides a highly biodegradable polyester containing hydrophilic groups and a preparation method thereof, wherein a small amount of highly hydrophilic groups are introduced into a low-aliphatic-content aliphatic-aromatic copolyester, and the hydrophilicity of the polymer is enhanced so that the copolyester can achieve high biodegradability at a low aliphatic segment content, thereby obtaining a copolyester having both the excellent thermal properties, mechanical properties and processing properties of aromatic polyesters and the high biodegradability of aliphatic polyesters.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a highly biodegradable polyester containing a hydrophilic group comprises the following steps: (1) using a first reactant, a second component, terephthalic acid and ethylene glycol as raw materials, to carry out an esterification or transesterification reaction to obtain an esterified product; the first reactant is a multifunctional small molecule having a hydrophilic group and additionally having two linking sites; the second component is an aliphatic polyol, polyacid, polyol acid or esterified product; (2) The esterified product is subjected to polycondensation reaction to obtain highly biodegradable polyester.

[0007] Preferably, the first reactant in step (1) is one of 2,2-dihydroxymethylpropionic acid, dimethyl sodium sulfosuccinate, 2-hydroxy-1,3,2-dioxaphospholane-2-oxide, dimethyl 5-hydroxyisophthalate, aminomalonic acid, citric acid monosalt, and metal salts of diethylene glycol 5-sulfoisophthalate. More preferably, it is 2-hydroxy-1,3,2-dioxaphospholane-2-oxide.

[0008] Preferably, the second component is selected from one or more of aliphatic polyols or aliphatic polyol polymers, aliphatic polyacids or esters thereof, and aliphatic polyol acids or esters thereof.

[0009] Preferably, the second component aliphatic polyol has a carbon number of 3-6 and a hydroxyl number of 2-4, and is further preferably propylene glycol, butylene glycol, glycerol, and pentaerythritol; the aliphatic polyol polymer is polyethylene glycol, polypropylene glycol, polyglycerol, polybutylene glycol, and polypentylene glycol, and is further preferably polyethylene glycol 400, polyethylene glycol 1000, polyethylene glycol 2000, and dipropylene glycol.

[0010] Preferably, the second component aliphatic polyacid has 2-8 carbon atoms and 2-3 carboxyl groups, more preferably succinic acid, glutaric acid, adipic acid, 1,4-cyclohexanedicarboxylic acid; the aliphatic polyacid ester is a methyl ester or ethylene glycol ester of the polyacid, more preferably dimethyl oxalate or diethylene glycol malonate.

[0011] Preferably, the second component aliphatic polyol acid has a carbon number of 2-6, and is further preferably glycolic acid, 3-hydroxypropionic acid, and citric acid; the aliphatic polyol acid ester is an alcohol acid with a carbon number of 2-6, and its methyl ester or an ester formed by intramolecular or intermolecular esterification, and is further preferably methyl glycolate, glycolide, oligoglycolic acid, and caprolactone.

[0012] Preferably, the molar ratio of the first reactant to terephthalic acid is (0.01-0.06):1; the molar ratio of the second component to terephthalic acid is (0.05-0.2):1.

[0013] Preferably, the conditions for the esterification or transesterification reaction in step (1) are: 200-230° C., 60-150 kPa nitrogen pressure, and reaction time of 2-5 h.

[0014] Preferably, in step (2), the esterified product is subjected to a condensation polymerization reaction with an antioxidant, a stabilizer and a catalyst.

[0015] Preferably, the polycondensation reaction conditions in step (2) are: 230-260° C. and a vacuum environment below 70 Pa for 3-8 hours.

[0016] The present invention also provides a highly biodegradable polyester containing a hydrophilic group, which is prepared by the above preparation method, has a crystallinity of more than 50% of that of ethylene terephthalate, a glass transition temperature higher than 65°C, a 5% thermal weight loss temperature above 380°C, and a 180-day biodegradability rate of more than 98%.

[0017] Therefore, the beneficial effects of the present invention are: (1) The biodegradability of the aromatic polyester is enhanced by the synergistic reaction of the first reactant having a highly hydrophilic group and the second component having an easily hydrolyzed aliphatic chain segment. The enhanced hydrophilicity and the easily hydrolyzed aliphatic ester bond enable the copolyester to achieve a relative biodegradability of more than 98% in an industrial composting environment.

[0018] (2) Through the synergistic effect of the hydrophilic groups, the amount of aliphatic chain segments introduced is greatly reduced compared with the existing biodegradable aromatic copolyesters. Compared with the mature biodegradable aromatic copolyester PBAT (the molar ratio of aliphatic butanediol adipate (BA) chain segments to aromatic butanediol terephthalate (BT) chain segments is 53 / 47, i.e., the aliphatic chain segments are 112.7% of the molar amount of the aromatic chain segments), this strategy only adds 5% to 20% of the molar amount of aliphatic chain segments relative to the aromatic chain segments to achieve a high biodegradation rate. Thus, the excellent properties of aromatic polyesters are effectively retained, including high crystallinity and high heat resistance. The crystallinity can reach more than 50% of that of typical aromatic polyesters (i.e., ethylene terephthalate), the glass transition temperature is higher than 65°C, and the 5% thermal weight loss temperature is above 380°C. This copolyester combines the excellent thermal properties, mechanical properties, and processing properties of aromatic polyesters with the high biodegradability of aliphatic polyesters. It reduces the amount of monomers other than terephthalic acid and ethylene glycol, has cost advantages, and at the same time expands the design ideas of biodegradable polyesters, which is conducive to the development of more biodegradable polyester structures. The excellent comprehensive performance is expected to optimize the existing application experience of biodegradable polyesters and expand the application scope of biodegradable polyesters. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below through specific embodiments.

[0020] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0021] Example 1. A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) Using a first reactant, a second component, terephthalic acid and ethylene glycol as raw materials, the molar ratio of the first reactant, the second component and terephthalic acid is (0.01-0.06):(0.05-0.2):1, and performing esterification or ester exchange reaction at 200-230° C. and 60-150 kPa nitrogen pressure for 2-5 hours to obtain an esterified product.

[0022] The first reactant is a multifunctional small molecule with a hydrophilic group and additionally with two linking sites, preferably one of the metal salts of 2,2-dihydroxymethylpropionic acid, dimethyl sodium sulfosuccinate, 2-hydroxy-1,3,2-dioxaphospholane-2-oxide, dimethyl 5-hydroxyisophthalate, aminomalonic acid, monocitrate, and 5-sulfonylisophthalic acid diethylene glycol ester, and more preferably 2-hydroxy-1,3,2-dioxaphospholane-2-oxide.

[0023] The second component is an aliphatic polyol, polyacid, polyol acid or ester; selected from one or more of aliphatic polyol or aliphatic polyol polymer, aliphatic polyacid or its ester, aliphatic polyol acid or its ester. Preferably, the carbon number of the aliphatic polyol of the second component is 3-6, the number of hydroxyl groups is 2-4, and more preferably propylene glycol, butanediol, glycerol, pentaerythritol; the aliphatic polyol polymer is polyethylene glycol, polypropylene glycol, polyglycerol, polybutylene glycol, polypentanediol, and more preferably polyethylene glycol 400, polyethylene glycol 1000, polyethylene glycol 2000, dipropylene glycol. Preferably, the carbon number of the aliphatic polybasic acid of the second component is 2-8, the carboxyl number is 2-3, and more preferably succinic acid, glutaric acid, adipic acid, 1,4-cyclohexanedicarboxylic acid; the aliphatic polybasic acid ester is the methyl ester or ethylene glycol ester of the polybasic acid, and more preferably dimethyl oxalate and diethylene glycol malonate. Preferably, the carbon number of the aliphatic polyol acid of the second component is 2-6, and more preferably glycolic acid, 3-hydroxypropionic acid, citric acid; the aliphatic polyol acid ester is the alcohol acid with a carbon number of 2-6, and its methyl ester or the ester formed by intramolecular or intermolecular esterification, and more preferably methyl glycolate, glycolide, oligoglycolic acid, caprolactone.

[0024] (2) The esterified product is subjected to polycondensation reaction at 230-260° C. and a vacuum environment below 70 Pa for 3-8 hours under the action of an antioxidant, a stabilizer and a catalyst to obtain a highly biodegradable polyester.

[0025] 2. A highly biodegradable polyester containing hydrophilic groups The present invention also provides a highly biodegradable polyester containing a hydrophilic group, which is prepared by the above preparation method, has a crystallinity of more than 50% of that of ethylene terephthalate, a glass transition temperature higher than 65°C, a 5% thermal weight loss temperature above 380°C, and a 180-day biodegradability rate of more than 98%.

[0026] The present invention introduces a small amount of highly hydrophilic groups into a low-aliphatic-content aliphatic-aromatic copolyester, and by enhancing the hydrophilicity of the polymer, the copolyester achieves high biodegradability at a low aliphatic segment content, thereby obtaining a copolyester that has both the excellent thermal properties, mechanical properties, and processing properties of aromatic polyesters and the high biodegradability of aliphatic polyesters, expands the design concept of biodegradable polyesters, is conducive to the development of more biodegradable polyester structures, and the excellent comprehensive performance is expected to optimize the existing application experience of biodegradable polyesters and expand the application scope of biodegradable polyesters.

[0027] Example 1 A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) 0.02 mol of 2,2-dimethylolpropionic acid as a reactive hydrophilic modifier, i.e., the first reactant, is directly mixed with 0.1 mol of dimethyl oxalate, 1.00 mol of terephthalic acid, and 1.12 mol of ethylene glycol, and then reacted at 200° C., 150 kPa pressure, and nitrogen atmosphere for 2 h to obtain a second esterification product; (2) Add 400 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite accounting for the total polyester mass, 1 ppm of triphenyl phosphite accounting for the total polyester mass, and 2 ppm of titanium element tetrabutyl titanate to the above-mentioned second esterified product, and carry out condensation reaction at 230°C and 70 Pa vacuum conditions for 8 hours to obtain a copolyester.

[0028] The copolyester and commercial PET polyester were used for differential scanning calorimetry (DSC) testing. Under nitrogen conditions, the temperature was raised to 300°C at 20°C / min, cooled to room temperature at 10°C / min, and then raised to 300°C at 10°C / min. The glass transition temperature (T g ) and melting peak enthalpy (ΔH m ) is collected from the second heating curve, and the copolyester T g At 72°C, ΔH m The polyester was used for thermal gravimetric analysis (TGA) test, and the temperature was raised to 500°C at 20°C / min under nitrogen conditions, and the temperature (T 5% ), to obtain the polyester T 5% The polyester exhibits good thermal stability.

[0029] The composting conditions were set according to ISO 14855 "Determination of the ultimate aerobic biodegradability and decomposition of plastic materials under controlled composting conditions - Method by analysis of released carbon", and the powder obtained by freeze-crushing the copolyester was subjected to a biodegradation test, and the degradation rate was found to reach 98% within 150 days.

[0030] Example 2 A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) 0.05 mol of sodium sulfosuccinate dimethyl ester is used as a reactive hydrophilic modifier, and after undergoing an ester exchange reaction with 0.1 mol of ethylene glycol, the mixture is uniformly mixed with 0.2 mol of polyethylene glycol (PEG1000), 1.00 mol of terephthalic acid and 9.94 mol of ethylene glycol, and then reacted at 230° C., 60 kPa pressure and nitrogen atmosphere for 5 hours to obtain a mixed ester; (2) 40 ppm of antioxidant 1010 accounting for the total polyester mass, 30 ppm of triphenyl phosphate accounting for the total polyester mass and 300 ppm of zinc acetate dihydrate are added to the above ester, and a condensation reaction is carried out at 260° C., 40 Pa vacuum conditions for 5 hours to obtain a copolyester.

[0031] The copolyester was used for DSC, TGA and biodegradation test according to the method described in Example 1. g 66℃, ΔH m Under the same test conditions, 80% of PET polyester, T 5% The temperature of the precipitate was 385°C, showing good crystallinity and thermal stability. Its biodegradability was measured to reach 98% in 180 days.

[0032] Example 3 A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) 0.03 mol of 2-hydroxy-1,3,2-dioxaphospholane-2-oxide was used as a reactive hydrophilic modifier, and was uniformly mixed with 0.15 mol of glycolide, 1.00 mol of terephthalic acid, and 1.03 mol of ethylene glycol, and then reacted at 200° C., 150 kPa pressure, and nitrogen atmosphere for 5 h to obtain an esterified product; (2) Add 200 ppm of 3-(2.4-di-tert-butylphenyl)phosphite accounting for the total polyester mass, 5 ppm of trioctyl phosphate accounting for the total polyester mass, and 10 ppm of titanium in the form of ethylene glycol to the above esterified product, and carry out polycondensation reaction at 230°C and 70 Pa under vacuum conditions for 7 hours to obtain a copolyester.

[0033] The copolyester was used for DSC, TGA and biodegradation test according to the method described in Example 1.g 86℃, ΔH m Under the same test conditions, T 5% The temperature of the precipitate was 427°C, showing good crystallinity and thermal stability. Its biodegradability was measured to reach 98% in 100 days.

[0034] Example 4 The difference from Example 3 is that the reactive hydrophilic modifier is 2,2-dimethylol propionic acid. The details are as follows: A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) 0.03 mol of 2,2-dimethylol propionic acid as a reactive hydrophilic modifier is uniformly mixed with 0.15 mol of glycolide, 1.00 mol of terephthalic acid and 1.03 mol of ethylene glycol, and then reacted at 200° C., 150 kPa pressure and nitrogen atmosphere for 5 hours to obtain an esterified product; (2) Add 200 ppm of 3-(2.4-di-tert-butylphenyl)phosphite accounting for the total polyester mass, 5 ppm of trioctyl phosphate accounting for the total polyester mass, and 10 ppm of titanium in the form of ethylene glycol to the above esterified product, and carry out polycondensation reaction at 230°C and 70 Pa under vacuum conditions for 7 hours to obtain a copolyester.

[0035] The copolyester was used for DSC, TGA and biodegradation test according to the method described in Example 1. g 86℃, ΔH m Under the same test conditions, T 5% The temperature of the precipitate was 427°C, showing good crystallinity and thermal stability. Its biodegradability was measured to reach 98% in 100 days.

[0036] Example 5 A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) 0.05 mol of 5-hydroxydimethylisophthalate as a reactive hydrophilic modifier is uniformly mixed with 0.1 mol of succinic acid, 0.1 mol of 1,4-cyclohexanedicarboxylic acid, 1.00 mol of terephthalic acid and 1.25 mol of ethylene glycol, and then reacted at 220° C., 150 kPa pressure and nitrogen atmosphere for 3 h to obtain a mixed ester; (2) To the above esterified product, 400 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, accounting for 30 ppm of the total polyester mass, and 8 ppm of titanium in the form of ethylene glycol were added, and a polycondensation reaction was carried out at 230° C. and 70 Pa under vacuum conditions for 7 h to obtain a copolyester.

[0037] The copolyester was used for DSC, TGA and biodegradation test according to the method described in Example 1. g 66℃, ΔH m Under the same test conditions, T 5% The temperature of the precipitate was 357°C, showing good crystallinity and thermal stability. Its biodegradability was measured to reach 99% in 150 days.

[0038] Example 6 A method for preparing a highly biodegradable polyester containing a hydrophilic group, comprising the following steps: (1) 0.05 mol of aminomalonic acid as a reactive hydrophilic modifier is uniformly mixed with 0.05 mol of propylene glycol, 0.1 mol of glycolic acid, 1.00 mol of terephthalic acid and 0.95 mol of ethylene glycol, and then reacted at 200° C., 150 kPa pressure and nitrogen atmosphere for 2 h to obtain an esterified product; (2) Add 200 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite accounting for the total polyester mass, 10 ppm of triphenyl phosphite accounting for the total polyester mass, and 50 ppm of zinc chloride as the zinc element to the above esterified product, and carry out polycondensation reaction at 230° C. and 70 Pa vacuum conditions for 8 h to obtain a copolyester.

[0039] The copolyester was used for DSC, TGA and biodegradation test according to the method described in Example 1. g At 72°C, ΔH m It is 62% of PET polyester under the same test conditions, T 5% The temperature of the precipitate was 397°C, showing good crystallinity and thermal stability. Its biodegradability was measured to reach 99% in 180 days.

[0040] Example 7 The difference from Example 1 is that the amount of the first reactant, the reactive hydrophilic modifier, exceeds the preferred range. Specifically: (1) 0.08 mol of 2,2-dihydroxymethylpropionic acid, 0.1 mol of dimethyl oxalate, 1.00 mol of terephthalic acid and 1.02 mol of ethylene glycol are uniformly mixed, and then reacted at 200° C., 150 kPa pressure, and nitrogen atmosphere for 2 hours to obtain an esterified product; (2) 400 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite accounting for the total polyester mass, 1 ppm of triphenyl phosphite accounting for the total polyester mass, and 2 ppm of titanium tetrabutyl titanate are added to the above esterified product, and a polycondensation reaction is carried out at 230° C. and 70 Pa vacuum conditions for 8 hours to obtain a copolyester.

[0041] The copolyester was subjected to DSC and TGA tests according to the method described in Example 1. The copolyester T g 52℃, ΔH m Under the same test conditions, T 5% is 320℃.

[0042] Example 8 The difference from Example 1 is that the amount of the second component exceeds the preferred range. Specifically: (1) 0.05 mol of 2,2-dihydroxymethylpropionic acid, 0.3 mol of dimethyl oxalate, 1.00 mol of terephthalic acid and 1.25 mol of ethylene glycol are uniformly mixed, and then reacted at 200° C., 150 kPa pressure, and nitrogen atmosphere for 2 hours to obtain an esterified product; (2) 400 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite accounting for the total polyester mass, 1 ppm of triphenyl phosphite accounting for the total polyester mass, and 2 ppm of titanium element tetrabutyl titanate are added to the above esterified product, and a polycondensation reaction is carried out at 230° C. and 70 Pa vacuum conditions for 8 hours to obtain a copolyester.

[0043] (3) The copolyester was subjected to DSC and TGA tests according to the method described in Example 1. The copolyester T g At 50℃, ΔH m It is 56% of PET polyester under the same test conditions, T 5% is 300℃.

[0044] Comparative Example Comparative Example 1 The difference from Example 1 is that the first reactant, the reactive hydrophilic modifier, is not introduced. Specifically: (1) 0.1 mol of dimethyl oxalate, 1.00 mol of terephthalic acid and 1.12 mol of ethylene glycol were uniformly mixed, and then reacted at 200° C., 150 kPa pressure and nitrogen atmosphere for 2 h to obtain an esterified product; (2) Add 400 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite accounting for the total polyester mass, 1 ppm of triphenyl phosphite accounting for the total polyester mass, and 2 ppm of titanium element tetrabutyl titanate to the above esterified product, and carry out polycondensation reaction at 230°C and 70 Pa vacuum conditions for 8 hours to obtain a copolyester.

[0045] The copolyester was used for DSC, TGA and biodegradation test according to the method described in Example 1. g 68℃, ΔH m It is 88% of PET polyester under the same test conditions, showing good crystallinity. 5%The temperature of the polyester film was 390°C, and the polyester exhibited good thermal stability. Its degradation rate was measured to be only 38% at 180 days. The polyesters obtained in Example 1 and Comparative Example 1 were respectively dissolved in chloroform to obtain a solution with a mass fraction of 5%, and then a flat film material was obtained by a solution casting method for water contact angle analysis. The water contact angle of the polyester film in Example 1 was measured to be 45°, and the water contact angle of the polyester film in Comparative Example 1 was 70°.

[0046] Comparative Example 2 The difference from Example 1 is that the second component, the easily hydrolyzed aliphatic monomer, is not introduced. Specifically: (1) 0.02 mol of 2,2-dihydroxymethylpropionic acid, 1.00 mol of terephthalic acid and 1.12 mol of ethylene glycol were uniformly mixed, and then reacted at 200° C., 150 kPa pressure, and nitrogen atmosphere for 2 h to obtain an esterified product; (2) Add 400 ppm of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite accounting for the total polyester mass, 1 ppm of triphenyl phosphite accounting for the total polyester mass, and 2 ppm of titanium element tetrabutyl titanate to the above esterified product, and carry out polycondensation reaction at 230°C and 70 Pa vacuum conditions for 8 hours to obtain a copolyester.

[0047] (3) The copolyester was subjected to DSC, TGA and biodegradation test according to the method described in Example 1. g At 72°C, ΔH m It is 98% of PET polyester under the same test conditions, showing good crystallinity. 5% The polyester exhibited good thermal stability at 398°C, and its degradation rate was only 22% at 180 days.

[0048] Results Analysis For the convenience of intuitive comparison, the performance data of the copolyesters prepared in various embodiments and comparative examples are summarized in the following table.

[0049] It can be seen from the above table that the copolyesters prepared in each embodiment of the present invention have excellent crystallinity, thermal stability and biodegradability. Compared with Example 1: (1) Compared with the copolyester without the introduction of the reactive hydrophilic modifier (Comparative Example 1), the introduction of the reactive hydrophilic modifier 2,2-dihydroxymethylpropionic acid (Example 1) can effectively improve the biodegradation rate of the copolyester. By preparing the obtained film, the measured water contact angle shows that the introduction of the reactive hydrophilic modifier effectively improves the hydrophilicity of the polyester, which is beneficial to the improvement of the biodegradation rate.

[0050] (2) Compared with the copolyester without the introduction of easily hydrolyzed aliphatic monomers (Comparative Example 2), the introduction of easily hydrolyzed aliphatic monomer dimethyl oxalate (Example 1) can effectively improve the biodegradation rate of the copolyester. Although the crystallinity and thermal stability of the copolyester obtained without the introduction of dimethyl oxalate monomer are very excellent, the degradation rate is obviously low, and the 180-day composting degradation rate is only 22%.

[0051] (3) Compared with the copolyester with a higher content of reactive hydrophilic modifier 2,2-dimethylol propionic acid (Example 6), adding an appropriate content of 2,2-dimethylol propionic acid (Example 1) ensures good thermal stability and crystallinity of the copolyester. However, the copolyester obtained in Example 6 has a decreased thermal stability and T 5% is 320℃.

[0052] (4) Compared with the copolyester with a high content of easily hydrolyzed aliphatic monomer (Example 7), the addition of an appropriate content of easily hydrolyzed aliphatic monomer dimethyl oxalate (Example 1) ensures good thermal stability and crystallinity of the copolyester. However, the copolyester obtained in Example 7 has a decreased thermal stability and T 5% Only 300℃.

[0053] (5) The first reactant in Example 3 is 2-hydroxy-1,3,2-dioxaphospholane-2-oxide, which has the highest biodegradation rate, reaching 98% in 100 days, and also has high glass transition temperature and thermal properties. It is the best solution of the present invention. It is speculated that this is because: the phosphorus heterocycle itself has a rigid skeleton, so the thermal properties are good. The phosphorus heterocycle also has ring tension, is prone to isomerization rearrangement reaction, and has good electron donation ability, so it is easy to degrade.

[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a highly biodegradable polyester containing a hydrophilic group, characterized in that: The steps include: (1) Using a first reactant, a second component, terephthalic acid and ethylene glycol as raw materials, an esterification or transesterification reaction is carried out to obtain an esterified product; the first reactant is a multifunctional small molecule with a hydrophilic group and two additional linking sites; the second component is an aliphatic polyol, polyacid, polyol acid or esterified product; (2) The esterified product undergoes polycondensation reaction to obtain highly biodegradable polyester.

2. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 1, characterized in that: Step (1) The first reactant is one of the metal salts of 2,2-dihydroxymethylpropionic acid, dimethyl sodium sulfosuccinate, 2-hydroxy-1,3,2-dioxaphospholane-2-oxide, dimethyl 5-hydroxyisophthalate, aminomalonic acid, monocitrate, and diethylene glycol 5-sulfonateisophthalate.

3. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 1, characterized in that: The second component is selected from one or more of aliphatic polyols or aliphatic polyol polymers, aliphatic polyacids or esters thereof, and aliphatic polyol acids or esters thereof.

4. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 3, characterized in that: The carbon number of the aliphatic polyol of the second component is 3-6 and the hydroxyl number is 2-4; the aliphatic polyol polymer is polyethylene glycol, polypropylene glycol, polyglycerol, polybutylene glycol, and polypentylene glycol.

5. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 3, characterized in that: The carbon number of the aliphatic polybasic acid of the second component is 2-8 and the carboxyl number is 2-3; the aliphatic polybasic acid ester is the methyl ester or ethylene glycol ester of the polybasic acid.

6. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 3, characterized in that: The carbon number of the aliphatic polyol acid of the second component is 2-6; the aliphatic polyol acid ester is an alcohol acid with a carbon number of 2-6.

7. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 1, 2 or 3, characterized in that: The molar ratio of the first reactant to terephthalic acid is (0.01-0.06):1; the molar ratio of the second component to terephthalic acid is (0.05-0.2):

1.

8. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 1, characterized in that: The conditions of the esterification or transesterification reaction in step (1) are: 200-230° C., 60-150 kPa nitrogen pressure, and reaction time of 2-5 h.

9. The method for preparing a highly biodegradable polyester containing a hydrophilic group according to claim 1 or 8, characterized in that: The conditions for the polycondensation reaction in step (2) are: 230-260° C. and a vacuum environment below 70 Pa for 3-8 hours.

10. A highly biodegradable polyester containing hydrophilic groups obtained by any one of the preparation methods of claims 1 to 9, characterized in that: The crystallinity is more than 50% of that of ethylene terephthalate, the glass transition temperature is higher than 65°C, the 5% thermal weight loss temperature is above 380°C, and the 180-day biodegradation rate is more than 98%.

Citation Information

Patent Citations

  • Aliphatic-aromatic polyesters, and articles made therefrom

    CN101735438A

  • Biodegradable polyester with high gas barrier property and preparation method and application thereof

    CN111848937A

  • Sulfonated aliphatic-aromatic copolyesters and shaped articles produced therefrom

    CN1829759A

  • Copolyetherester compositions containing hydroxyalkanoic acids and shaped articles produced therefrom

    CN1980976A

  • Sulfonated copolyetherester compositions from hydroxyalkanoic acids and shaped articles produced therefrom

    CN1980977A